‘The something else was really valuable’: how a gallery education programme worked with primary schools during the pandemic - Gilliam, Maddy (2024)
Gallery education programmes have holistic benefits that support children’s social and emotional needs. These needs were particularly important during the disruption of the pandemic. This thesis explores how a gallery education programme changed to support primary teachers during the pandemic, when the normal ways of doing things, for example, being in the gallery, were disrupted. The literature has established that partnerships between schools and the cultural sector are beneficial, however, they can be challenging. During the pandemic, both the cultural sector and schools experienced a disruption – how did gallery educators respond to the uncertain context, and what did teachers think of this response? This study aimed to research how a gallery education team changed their practice through a relationship with teachers during this tumultuous period. The study took an ethnographic approach with the Schools and Teachers team at Tate gallery during a period of remote working. This included observations of online meetings and events, email correspondence and working documents, as well as interviews with gallery educators and teachers interacting with the programme. The thesis uses communities of practice to understand the gallery educators’ practice as continually changing in relation to a new social and institutional context. The pandemic context increased the importance of connecting to primary teachers and school practice to help understand and respond to the new reality. The gallery education team wanted teachers to explore non-directive artist practice as a teaching approach. Primary teachers valued what was on offer but did not alter how they taught. After a period of change, the gallery education practice largely returned to a pre-pandemic practice. The values and difference of gallery education became important to safeguard and maintain, requiring teachers to ‘translate’ experiences into the classroom. This research suggests that the gallery education sector needs to better articulate its value for the primary classroom and offer more ‘ways in’ for teachers.